Ewing's sarcoma of the mandible in a young child - Brazão-Silva,Marco Túllio (2010)
Ewing's sarcoma (ES) is a malignancy primarily affecting bone tissue that is commonly diagnosed in adolescents and young adults. Its occurrence in the head and neck region is unusual and generally involves the mandible and maxilla. An extensive review of the literature shows only few cases of the oral ES in patients under the age of 5. This paper reports a rare case of ES of the mandible in a 4-year-old girl, which had been previously misdiagnosed and treated as a dental abscess. In the clinical examination, a hard immobile expansive mass of 5 cm in diameter was observed on the left side of the mandible. Radiographic examination revealed a radiolucent lesion with ill-defined borders and wide vestibular bone plate destruction. Microscopically, the tumor was composed by monotonous small round cells that exhibited immunoreactivity for CD99, vimentin and pancytokeratin. The patient was subjected to multiagent chemotherapy with ifosfamide, carboplatin, etoposide, vincristine, cyclophosfamide and doxorrubycin (VAC/ICE regimen). However, after the first chemotherapeutic cycle, the patient died due to disseminated infection. This case elucidates the importance of professional knowledge of the relevant aspects of malignant lesions such as ES.